Ekstrakurikuler Islamic Centre Sebagai Wahana Integrasi Pembiasaan Sikap Ilmiah dan Bina Taqwa Peserta Didik di SMA Umum - Tamara, Nadiya Erike; Ulfatin, Nurul; Imron, Ali; Timan, Agus (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2024)
Abstract: The purpose of this research is to describe the intracurricular and extracurricular Islamic Center as a means of integrating the habituation of scientific attitudes and fostering piety of students at public SMA of 1 Kesamben, Blitar. This study uses a qualitative approach with a case study type of research. Data collection was carried out using interview techniques, observation, and documentary studies. Data analysis was carried out interactively starting from data collection, condensation, data presentation, and drawing conclusions. The results of this study are (1) a form of scientific attitude that is habituated to students at school can be carried out through routine habituation activities and habituation during learning; (2) the values of taqwa that are fostered in students include a series of habituation activities, namely mandatory wearing of the hijab, praying before and after carrying out lessons, performing obligatory and sunnah prayers in congregation, and morning tadarus; (3) types of Islamic Center extracurricular activities developed in schools, namely routine training once a week, hadrah or al-banjari, thaharah by cleaning the mosque environment, Al-Quran Reading Arts (SBQ), Commemoration of Islamic Holidays (PHBI), attending MCRB (Majelis Cinta Rosul Blitar), competitions in the field of religion and compensation for orphans; (4) Islamic Center extracurriculars in integrating the habituation of scientific attitudes and fostering piety there are several habits; (5) the integration strategy of habituation of scientific attitudes and fostering piety through Islamic Center extracurricular activities includes habituation and exemplary activities by coaches in Islamic Center extracurricular activitiesKeywords: intracurricular; extracurriculars; scientific attitude; development of taqwa Abstrak: Tujuan dari penelitian ini yaitu untuk mendeskripsikan mengenai intrakurikuler dan ekstrakurikuler Islamic Centre sebagai wahana integrasi pembiasaan sikap ilmiah dan bina taqwa peserta didik di SMA Negeri 1 Kesamben, Blitar. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian studi kasus. Pengumpulan data dilakukan dengan teknik wawancara, observasi, dan studi dokumenter. Analisis data dilakukan secara interaktif mulai dari pengumpulan data, kondensasi, penyajian data, dan penarikan kesimpulan. Hasil dari penelitian ini adalah (1) bentuk sikap ilmiah yang dibiasakan pada diri peserta didik di sekolah dapat dilakukan melalui kegiatan pembiasaan rutin dan dilakukan pembiasaan saat pembelajaran; (2) nilai-nilai taqwa yang dibina pada diri peserta didik meliputi rangkaian kegiatan pembiasaan, yakni peraturan wajib memakai hijab, berdoa sebelum dan sesudah melakukan pembelajaran, melakukan ibadah sholat wajib dan sunnah berjamaah, dan tadarus pagi; (3) jenis kegiatan ekstrakurikuler Islamic Centre yang dikembangkan di sekolah, yaitu latihan rutin satu minggu sekali, hadrah atau al-banjari, thaharah dengan membersihkan lingkungan mushola, Seni Baca Al-Quran (SBQ), Peringatan Hari Besar Islam (PHBI), mengikuti MCRB (Majelis Cinta Rosul Blitar), lomba bidang keagamaan dan santunan anak yatim; (4) ekstrakurikuler Islamic Centre dalam mengintegrasikan pembiasaan sikap ilmiah dan bina taqwa terdapat beberapa pembiasaan; (5) strategi integrasi pembiasaan sikap ilmiah dan bina taqwa melalui kegiatan ekstrakurikuler Islamic Centre meliputi kegiatan pembiasaan dan keteladanan oleh pembina dalam kegiatan ekstrakurikuler Islamic Centre.Kata kunci: intrakurikuler; ekstrakurikuler; sikap ilmiah; bina taqwa